STUDY OF BUYING BEHAVIOUR OF CUSTOMERS IN DIGITALISATION OF RETAIL SECTORS - Batra, Pooja; S N Mahapatra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The increasing disruption of traditional business models through digital technologies offers both significant opportunities and challenges for retail businesses and their network partners. Digital transformation – the process of converting traditional analog operations, procedures, organizational tasks, and managerial processes into digital forms to create value for customers, employees, and other stakeholders – has become a critical necessity. This review article helps to get vast knowledge of research in field of digital transformation, customer behaviourally aspect towards digitalization in retail. Topic will cover customer behaviourally pattern for digital technologies, impact of sensory marketing, service role in automation, mechanoid environment, segmenting and strategic implication of latest technologies in business.